Proxy or Durable power of attorney for health care: Canon 668 - Vodenberger, Victoria (Roman Replies and CLSA Advisory Opinions 2011, 2011)
"Recently one of our Sisters suddenly became seriously ill and needed hospitalization. Due to complications, there were important choices to be made concerning her treatment. Sister has a health care proxy who is not a member of our religious institute. Soon it became clear that person and our Provincial superior had differing opinions about what treatment Sister should receive. Which persons opinion takes priority? Also, is it advantageous and even necessary for a woman religious to appoint someone as her power of attorney for health care?"